Khitbah perkawinan perspektf sosio antropologi - Arifin, Muhammad Nur (Maliki Interdisciplinary Journal, 2025)
Khitbah, or engagement, is the initial stage in the marriage process that is detailed in Islamic law. This concept is rooted in religious values, customs, and the social structure of society, with the primary aim of inviting the establishment of a household. In socio-anthropological studies, khitbah is viewed as a cultural phenomenon that continues to evolve, reflecting adaptations to changing values and norms. However, khitbah does not have legal consequences like marriage contracts, so the interaction between prospective partners must still adhere to sharia boundaries to prevent violations such as khalwat or adultery. This study also highlights how the tradition of engagement developed in various regions of Indonesia before the arrival of Islam, influenced by local beliefs such as animism, dynamism, Hinduism, and Buddhism. Prohibitions and restrictions in khitbah have wisdom in preserving honor and minimizing temptation before the marriage contract is conducted.